IMPACT OF SOCIAL MEDIA INFLUENCERS ON PURCHASING INTENTION TOWARDS PET PRODUCTS. A QUANTITATIVE STUDY AMONG FEMALES IN MALAYSIA - Wei , Liew Yee; Singh , Jugindar Singh Kartar; Kularajasingam, Janitha (Electronic Journal of Business and Management, 2021)
Marketers are increasingly leveraging social media influencers to boost revenue, but the specific impact on the pet product industry remains under-researched. This study explores how influencer attributes—trustworthiness, attractiveness, expertise, source respect, and source similarity—affect the purchasing intentions of Malaysian females. Using a quantitative approach and convenience sampling, primary data was collected from 202 respondents. The findings revealed that only source attractiveness and source similarity were significant predictors of purchase intention, with source similarity having the highest impact. Surprisingly, trustworthiness, expertise, and respect were found to be insignificant. This study provides new insights for pet product retailers on selecting the right influencers based on relatability and attractiveness.